Chemical and pharmacological evaluation of the effectiveness of enalapril maleate in exertional angina pectoris in elderly and senile patients - Belay, I. M.; Stets, R. V.; Gnitko, I. V. (Zaporozhye Medical Journal, 2013)
The long-term administration of enalapril maleate in complex therapy of exertional angina pectoris in elderly persons showed antiischemic, antiarrhythmic effects of angiotensin converting enzyme inhibitors. Using chemical-pharmacological analysis the administration of enalapril against the background of basic therapy in patients with ischemic heart disease was grounded.